2017
DOI: 10.18632/oncotarget.v8i32
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Extensive studies have led to the identification of protein-protein interaction (PPI) cores and intersections that are critical for the acquisition and maintenance of properties of malignant transformation [1]. With technological advances in PPI modulator discovery and validation of PPI-targeting agents, for instance, several small-molecule PPI antagonists that target the interactions of MDM2/p53, XIAP/caspase-9 and BCL2/beclin1 are being studied in clinical trials for cancer patients; targeting of PPI interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…With respect to the other diagnostic techniques for MPM diagnosis, our diagnostic approach, namely ATR-FTIR spectroscopy coupled with multivariate analysis, is a nondestructive, fast, reliable, relatively low-cost, operator-independent, and highly reproducible method. 82 Therefore, we propose that this approach has a promising potential for diagnosis with a higher accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the other diagnostic techniques for MPM diagnosis, our diagnostic approach, namely ATR-FTIR spectroscopy coupled with multivariate analysis, is a nondestructive, fast, reliable, relatively low-cost, operator-independent, and highly reproducible method. 82 Therefore, we propose that this approach has a promising potential for diagnosis with a higher accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by weakening the PAR3/PAR6/aPKC polar protein complex as well as promoting EMT, SHP2 can encourage the migration of prostate tumor cells both in vivo and in vitro , as well as the spread of prostate cancer ( 144 ). Targeting SHP2 increases expression of PD-L1 and human leukocyte antigen (HLA) ABC in prostate cancer cells by phosphorylating STAT1, which is relevant to immune-cell interaction and immunotherapy tactics ( 145 ).…”
Section: The Role Of Shp2 In Different Solid Tumor Entitiesmentioning
confidence: 99%
“…Common parameters in DWI assessments include pure molecular diffusion (D) and perfusion-related diffusion (D*). Research has indicated that elevated D* values correlate with increased angiogenesis and parenchymal perfusion in NPC ( 93 , 94 ). The D value was significantly decreased in primary NPC; however, elevated D and D* values indicated radiosensitivity of the cancer, suggesting a favorable prognosis for the tumor.…”
Section: Angiogenic Application In Npcmentioning
confidence: 99%
“…Studies have confirmed that apatinib can achieve good efficacy in the treatment of NPC patients with lung metastasis and advanced VEGFR-2-negative NPC while ensuring safety ( 107 ). Apatinib can be used not only as a monotherapy but also in combination with radiotherapy or chemotherapy to treat patients with NPC, effectively enhancing its anti-vascular effects ( 29 , 108 ). Famitinib combined with radiotherapy increased the radiosensitivity of NPC cells by inhibiting angiogenesis ( 109 ).…”
Section: Angiogenic Application In Npcmentioning
confidence: 99%